The Effect of Board and Ownership Structure on the Possibility of Financial Distress - Joanne Jovita Jodjana; Sherin Nathaniel; Rinaningsih Rinaningsih; Titin Pranoto (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine the effect of corporate governance, specifically relating to the ownership structure and board structure, on the possibility of financial distress.Design/Methodology/Approach: The sample used in this study are companies listed on the Indonesia Stock Exchange (IDX) from 2015 to 2019, excluding the financial industry. Conditional logistic regression is used as the study uses paired data based on the total assets of the company.Research findings: The results of this study indicate that board ownership, independent commissioners, and the board of directors can increase the likelihood of financial distress. On the other hand, institutional ownership and concentrated ownership are proven to have no effect on the likelihood of financial distress. The results of sensitivity testing using logistic regression showed different results on the variable institutional ownership, which is that institutional ownership can increase the likelihood of financial distress. Meanwhile, the other variables showed the same outcome as the main regression used in this study.Theoretical contribution/Originality: This study contributes to the knowledge on the relationship of board ownership, institutional ownership, concentrated ownership, independent commissioners and board size and the possibility of financial distress. Also, this research found that the provision of incentives in the form of shares to the board may not be an effective way to overcome financial distress in Indonesian firms.